Stability in the cumulative incidence, severity and mortality of 101 cases of invasive mucormycosis in high‐risk patients from 1995 to 2011: a comparison of eras immediately before and after the availability of voriconazole and echinocandin‐amphotericin combination therapies. Issue 11 (18th July 2014) - Abidi, Maheen Z.; Sohail, Muhammad R.; Cummins, Nathan; Wilhelm, Mark; Wengenack, Nancy; Brumble, Lisa; Shah, Harshal; Jane Hata, Donna; McCullough, Ann; Wendel, Amy; Vikram, Holenarasipur R.; Kusne, Shimon; et al.
Summary As invasive mucormycosis (IM) numbers rise, clinicians suspect prior voriconazole worsens IM incidence and severity, and believe combination anti‐fungal therapy improves IM survival. To compare the cumulative incidence (CI), severity and mortality of IM in eras immediately before and after the commercial availability of voriconazole all IM cases from 1995 to 2011 were analysed across four risk‐groups (hematologic/oncologic malignancy (H/O), stem cell transplantation (SCT), solid organ transplantation (SOT) and other), and two eras, E1 (1995–2003) and E2, (2004–2011). Of 101 IM cases, (79 proven, 22 probable): 30 were in E1 (3.3/year) and 71 in E2 (8.9/year). Between eras, the proportion with H/O or SCT rose from 47% to 73%, while 'other' dropped from 33% to 11% (P = 0.036). Between eras, the CI of IM did not significantly increase in SCT (P = 0.27) or SOT (P = 0.30), and patterns of anatomic location (P = 0.122) and surgical debridement (P = 0.200) were similar. Significantly more patients received amphotericin‐echinocandin combination therapy in E2 (31% vs. 5%, P = 0.01); however, 90‐day survival did not improve (54% vs. 59%, P = 0.67). Since 2003, the rise of IM reflects increasing numbers at risk, not prior use of voriconazole. Frequent combination of anti‐fungal therapy has not improved survival.